2013
DOI: 10.1007/s00024-012-0630-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Summer Ozone Observations at a High Mountain Site in Central Italy (Campo Imperatore, 2388 m a.s.l.)

Abstract: Abstract-Tropospheric ozone (O 3 ) is an important atmospheric pollutant and climate forcer. The Mediterranean basin is a hot-spot region in terms of short-term O 3 distribution, with frequent episodes of high tropospheric O 3 , especially during summer. To improve the characterisation of summer O 3 variability in the Mediterranean area, during the period 6-27 August 2009 an experimental campaign was conducted at Campo Imperatore, Mt Portella (CMP), a high mountain site (2,388 m a.s.l.) located in the central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…At the high Alpine site Jungfraujoch (3450 m MSL) in Switzerland, for instance, recent studies with a variety of observations and methods (in situ radon and trace gas measurements; aerosol-layer detection by lidar; Lagrangian particle dispersion model) estimated that the station is under the influence of boundary layer emissions for 40%-60% of the year, with a significant impact on in situ aerosol measurements as compared with free-tropospheric conditions (Collaud-Coen et al 2011;Herrmann et al 2015;Poltera et al 2017). Cristofanelli et al (2013) analyzed summer ozone (O 3 ) observations at a mountain site (2388 m MSL) in the central Italian Apennines and found that the site was significantly affected by air masses from the Mediterranean basin for 32% of the time. Vertical exchange processes made complex by mountainous terrain (Rotach et al 2015;Steyn et al 2013) are less well understood than processes on flat terrain (Zardi and Whiteman 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At the high Alpine site Jungfraujoch (3450 m MSL) in Switzerland, for instance, recent studies with a variety of observations and methods (in situ radon and trace gas measurements; aerosol-layer detection by lidar; Lagrangian particle dispersion model) estimated that the station is under the influence of boundary layer emissions for 40%-60% of the year, with a significant impact on in situ aerosol measurements as compared with free-tropospheric conditions (Collaud-Coen et al 2011;Herrmann et al 2015;Poltera et al 2017). Cristofanelli et al (2013) analyzed summer ozone (O 3 ) observations at a mountain site (2388 m MSL) in the central Italian Apennines and found that the site was significantly affected by air masses from the Mediterranean basin for 32% of the time. Vertical exchange processes made complex by mountainous terrain (Rotach et al 2015;Steyn et al 2013) are less well understood than processes on flat terrain (Zardi and Whiteman 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Stratospheric ozone can protect the Earth’s surface from dangerous ultraviolet radiation from the sun, but ground-level ozone (O 3 ) is an important atmospheric pollutant and agent of climate change [ 1 ]. Ground-level ozone is mainly produced by a complex photochemical reaction between nitrogen oxides (NO X = NO + NO 2 ) and volatile organic compounds (VOCs) under strong solar radiation.…”
Section: Introductionmentioning
confidence: 99%
“…In Cristofanelli et al (2013) differences of ozone concentrations are shown at Campo Imperatore, in the Abruzzi massif, depending on whether air masses come from the Mediterranean sea or from the European continent. Continental air masses tend to bring air masses with higher ozone values.…”
Section: Introductionmentioning
confidence: 99%
“…Another common way to analyse air composition data at mountain sites is to track (usually at a larger continental scale) the air masses using backward trajectories or dispersion models. The composition measurements are then sorted by geographical source regions (e.g., Cui et al (2011) and Loeoev et al (2008) at the Jungfraujoch; Cristofanelli et al (2013) at Campo Imperatore, central Italy; Perry et al (1999) at Mauna Loa, Hawaii; among many). The two studies at the Jungfraujoch highlight differences in ozone concentration and other chemical components such as CH 4 and CO (Loeoev et al, 2008), depending on whether air masses were influenced by the European planetary boundary limit or were long-range advected to Jungfraujoch.…”
Section: Introductionmentioning
confidence: 99%